A scan for genes associated with cancer mortality and longevity in pedigree dog breeds - Aoife Doherty; Inês Lopes; Christopher T. Ford; Gianni Monaco; Patrick Guest; João Pedro de Magalhães (Mammalian Genome, 2020)
Selective breeding of the domestic dog ( Canis lupus familiaris ) rigidly retains desirable features, and could inadvertently fix disease-causing variants within a breed. We combine phenotypic data from > 72,000 dogs with a large genotypic dataset to search for genes associated with cancer mortality and longevity in pedigree dog breeds. We validated previous findings that breeds with higher average body weight have higher cancer mortality rates and lower life expectancy. We identified a significant positive correlation between life span and cancer mortality residuals corrected for body weight, implying that long-lived breeds die more frequently from cancer compared to short-lived breeds. We replicated a number of known genetic associations with body weight ( IGF1 , GHR , CD36 , SMAD2 and IGF2BP2 ). Subsequently, we identified five genetic variants in known cancer-related genes (located within SIPA1 , ADCY7 and ARNT2 ) that could be associated with cancer mortality residuals corrected for confounding factors. One putative genetic variant was marginally significantly associated with longevity residuals that had been corrected for the effects of body weight; this genetic variant is located within PRDX1 , a peroxiredoxin that belongs to an emerging class of pro-longevity associated genes. This research should be considered as an exploratory analysis to uncover associations between genes and longevity/cancer mortality.

A synoptic climatology of strong along‐channel winds on the Coast of British Columbia, Canada - Talaat Bakri; Peter Jackson; Ford Doherty (International Journal of Climatology, 2017)
A synoptic climatology using mean sea level pressure and 500‐ hPa geopotential height composites is conducted for strong along‐channel winds that occur through five of the channels dissecting British Columbia's coast. Seasonal (winter, summer) and directional (inflow, air moving from the coast inland; outflow, air moving from inland towards the coast) partitioning of the winds, results in four distinct along‐channel winds that occur: summertime inflow, summertime outflow, wintertime inflow and wintertime outflow. Composite analyses using reanalysis data and in situ observations are used to examine each wind type at all locations. Wintertime composites produce patterns that are distinct from the overall winter climatology, in which outflows occur when an arctic surface high‐pressure area on the inland side of the coastal mountains is accompanied by the presence of an area of low surface pressure in the northeastern Pacific. Inflow composites in the winter indicate low‐pressure areas associated with mid‐latitude cyclones over the Gulf of Alaska. Summertime composites are similar to the overall summer climatology; therefore, other approaches are applied to explain these winds. We analyse 104 summertime inflow events at three locations using surface analysis charts for 13 summer seasons. The analysis reveals the importance of fronts at the time of inflows, with fronts associated with almost half of the events. Non‐hierarchical clustering analysis is applied for the summertime inflow events. The clustering analysis gives a better explanation of the summertime inflows than the composites. This is achieved by grouping events into different clusters, allowing for better illustration of the variance between the clusters.